Rhamnolipid Biosurfactant against Fusarium verticillioides to Control Stalk and Ear Rot Disease of Maize - Borah, Siddhartha N.; Goswami, Debahuti; Sarma, Hridip K.; Cameotra, Swaranjit S.; Deka, Suresh (Frontiers in Microbiology, 2016)
Antifungal activity of rhamnolipids (RLs) has been widely studied against many plant pathogenic fungi, but not against Fusarium verticillioides, a major pathogen of maize (Zea mays L.). F. verticillioides causes stalk and ear rot of maize or asymptomatically colonizes the plant and ears resulting in moderate to heavy crop loss throughout the world. F. verticillioides produces fumonisin mycotoxins, reported carcinogens, which makes the contaminated ears unsuitable for consumption. In this study, the RL produced using glucose as sole carbon source was characterized by FTIR and LCMS analyses and its antifungal activity against F. verticillioides was evaluated in vitro on maize stalks and seeds. Further, the effect of RL on the mycelia of F. verticillioides was investigated by scanning electron microscopy which revealed visible damage to the mycelial structure as compared to control samples. In planta, treatment of maize seeds with a RL concentration of 50 mg l-1 resulted in improved biomass and fruiting compared to those of healthy control plants and complete suppression of characteristic disease symptoms and colonization of maize by F. verticillioides. The study highlights the potential of RLs to be used for an effective biocontrol strategy against colonization of maize plant by F. verticillioides.